Liver Injury in COVID-19: A Direct Hit or Collateral Damage? - Vairappan, Balasubramaniyan; Wright, Gavin; Corrigal, Douglas; TS, Ravikumar (Infectious Disorders - Drug Targets, 2022)
SARS-CoV-2 is a novel coronavirus that has been identified, in December 2019, in Wuhan, China, and since it has become a worldwide pandemic, it has imposed far-reaching impacts on global human health and socio-economic activity. Worldwide, over 4 million Covid-19 related deaths were reported until September 2021. Recently published case studies have reported that Covid-19 patients develop different degrees of liver dysfunction. Inevitably, in hospitalized Covid-19 patients who develop acute liver derangement, there are a plethora of potential pathogenic causes such as direct-viral, immune-driven, and drug-induced and/or ischaemic liver injury. Patients with advanced chronic liver diseases (e.g., cirrhosis) and/or autoimmune liver disease have a poor immune function and associated poorer outcomes compared to other critically ill cohorts. However, largely any immediate liver derangement tends to be relatively mild, and as such, any de novo liver injury may not be a significant feature of Covid-19. There is an immediate necessity, therefore, to better understand the liver-specific pathophysiology of COVID-19. This review focuses on the up-to-date information regarding Covid-19 and associated indices for liver dysfunction, possible mechanisms, and potential drug targeted therapies in Covid-19 patients with and without liver dysfunction. PubMed database was used to perform an extensive literature search using the keywords liver and SARS-CoV-2, liver and Covid-19, Covid 19 and treatment, etc.
Keywords: inflammation